PEMBERIAN RELAKSASI BENSON TERHADAP PENURUNAN NYERI PASIEN POST OPERASI FRAKTUR FEMUR DI RUMAH SAKIT UMUM DAERAH MEURAXA BANDA ACEH - Nurhayati Nurhayati; Dewi Marianthi; Desiana Desiana; Raima Maulita (Poltekkes Kemenkes Aceh, 2022)
Pain in postoperative Femur Fracture patients must be addressed immediately because it has an impact on the patient's healing process, because it can affect psychological and physiological conditions. Benson relaxation is one of the methods that can reduce pain, this technique is able to reduce the activity of the sympathetic nerves that control pain, causing a feeling of calm and comfort and will affect the decrease in pain intensity. The purpose of this study was to determine the effect of Benson Relaxation on reducing pain intensity in post-femoral fracture surgery patients at Meuraxa Hospital Banda Aceh in 2019. The method used in this study was a quasi-experimental pre test and post test one group, the number of samples in this study was 14 respondents. Consecutive sampling sampling technique. The time of this research was carried out on June 04 to July 22, 2019. The data were processed using paired t-test and Independent t-test statistical tests. The results of the study used paired t-test statistical tests. It shows that there is a significant difference in pain intensity before and after Benson Relaxation in postoperative femur fracture patients with p value 0.000 (P < 0.05), and the results of the study using the Independent t-test statistic test showed that there was a significant difference in pain intensity between the experimental group and the experimental group. control group of postoperative Femur Fracture patients with p value 0.010 (P < 0.05), so it can be concluded that there is a significant effect on pain intensity after Benson Relaxation in postoperative Femur Fracture patients. It is hoped that patients and nurses can apply the Benson Relaxation Technique after Fracture surgery.